Tanggung Gugat Perusahaan Atas Hubungan Jual Beli Pihak Ketiga yang Menjanjikan Harga di Bawah Harga Resmi kepada Pembeli: (Studi Kasus PT ANTAM Melawan Budi Said) - Annisaa Azzahra; Bima Satriojati; Jasmine Putri Sabillah; Tazkia Nanini (Jurnal Hukum Lex Generalis, 2021)
The position case originated from a gold trading agreement in which Eksi Anggraeni sold gold weighing 7 tons below the official price of a company named PT ANTAM to Budi Said. However, Eksi Anggraeni is not an employee of PT ANTAM. When there was a shipment of gold from Eksi Anggraeni to Budi Said, it turned out that the weight of gold sent by Eksi Anggraeni was not in accordance with what had been promised in the beginning. Then, Budi Said sued PT ANTAM with a lawsuit of Unlawful Acts. PT ANTAM should not be liable for the non-fulfillment of achievements by Eksi Anggraeni to Budi Said.